Pediatric Acute Respiratory Distress Syndrome: Fibrosis versus Repair - Im, Daniel; Shi, Wei; Driscoll, Barbara (Frontiers in Pediatrics, 2016)
Clinical and basic experimental approaches to pediatric acute lung injury (ALI), including acute respiratory distress syndrome (ARDS), have historically focused on acute care and management of the patient. Additional efforts have focused on the etiology of pediatric ALI and ARDS, clinically defined as diffuse, bilateral diseases of the lung that compromise function leading to severe hypoxemia within seven days of defined insult. Insults can include ancillary events related to prematurity, can follow trauma and/or transfusion, or can present as sequelae of pulmonary infections and cardiovascular disease and/or injury. Pediatric ALI/ARDS remains one of the leading causes of infant and childhood morbidity and mortality, particularly in the developing world. Though incidence is relatively low, ranging from 2.9-9.5 cases/100,000 patients/year, mortality remains high, approaching 35% in some studies. However, this is a significant decrease from the historical mortality rate of over 50%. Several decades of advances in acute management and treatment, as well as better understanding of approaches to ventilation, oxygenation and surfactant regulation, have contributed to improvements in patient recovery. As such, there is a burgeoning interest in the long term impact of pediatric ALI/ARDS. Chronic pulmonary deficiencies in survivors appear to be caused by inappropriate injury repair, with fibrosis and predisposition to emphysema arising as irreversible secondary events that can severely compromise pulmonary development and function, as well as the overall health of the patient. In this chapter, the long term effectiveness of current treatments will be examined, as will the potential efficacy of novel, acute and long term therapies that support repair and delay or even impede the onset of secondary events, including fibrosis.